Pengaruh Model Pembelajaran Kooperatif Tipe Nht Terhadap Kemampuan Berpikir Kritis dan Keaktifan Peserta Didik - Niken Ayu Setyorini; Budi Adjar Pranoto; Dedi Romli Triputra (Peneliti.net, 2022)
This study aims to determine the effect of the NHT cooperative learning model on the critical thinking skills and activeness of students. The method used in this research is by experiment. The sampling technique used is Systematic Sampling. The subject matter used in the study is the content of learning Mathematics with the materials for Perimeter and Area of ​​Square and Rectangle. This study was analyzed using t test. The results obtained are the dependent variable Y1 obtained a significance value of 0.000 <0.05. Obtained the value of tcount = 9.312 while ttable = 2.101 then Ho is rejected and Ha is accepted because tcount > ttable. Thus, the Numbered Head Together (NHT) learning model has an influence on the critical thinking skills of fourth grade students on the mathematics content at SD Negeri Siasem 03. Then the dependent variable Y2 obtained a value of 0.145 > 0.05. The value of tcount = 1,522 while ttable = 2.101 means that Ho is accepted and Ha is rejected because tcount < ttable. Thus, the Numbered Head Together (NHT) learning model has no effect on the activity of fourth grade students in the mathematics content at SD Negeri Siasem 03 than the use of conventional learning models.